Biostimulant activity of humic acids derived from goat manure vermicompost and lignite in relation to their structure and interaction with a PGPR strain under semiarid conditions (2023)
The use of humified organic matter (HOM)-based plant biostimulants and plant growth-promoting rhizobacteria (PGPR) has emerged as a promising approach to enhance agricultural productivity in arid and semiarid environments. However, the bioactivity of humic stimulants varies based on their chemical composition, and the synergistic effects of co-applying these biostimulants remain to be fully elucidated. In this research, we investigated the structural and bioactive characteristics of humic acids derived from goat manure vermicompost (HAVC) and lignite coal (HAC). Additionally, we explored the plant growth-promoting effects of each humic acid (HA) in conjunction with the Bacillus mycoides strain BSC25 (Bm) on corn plants in arid conditions. To assess the relationship between structure and bioactivity, we determined the supramolecular composition of the HAs and evaluated their effectiveness through a corn coleoptile elongation test. Subsequently, we conducted biostimulation tests on maize seedlings in a growth chamber and performed a field-based biostimulation test in a semi-arid region. Notably, HACs exhibited coleoptile elongation at lower concentrations (25-50 mg LC) compared to HAVCs, which required higher concentrations (100-200 mg LC) to achieve the same effect. These outcomes correlated with the supramolecular composition of HAs. The bioactivity of HACs was linked to their oxygen content, aromatic and carboxylic groups, whereas HAVCs' bioactivity was associated with their carbohydrate, aliphatic carbon, and hydrogen content. The application of both HAs, together with Bm, resulted in enhanced corn leaf biomass production in the growth chamber and under field conditions. This effect can be attributed to the hormone-like actions of HA and the PGPR activity of Bm. Interestingly, despite foliar application, HAs displayed bioactivity at the root level, as evidenced by increased root biomass in the field. These results indicate a PGPR effect of Bm that remained unaltered with co-application of HAVC. However, the joint application of Bm-HAC and Bm-HAVC reversed the positive effect of Bm on corn production under field conditions. This outcome likely relates to the hormone-like effects of HA and potential additive effects following Bm inoculation.